Enhancing initial teacher education through poetry: Explorations of the pedagogical practices of three poet-educators. (November 2022) - Creely, Edwin; Bao, Dat; Waterhouse, Peter
Abstract: Evidence of the importance of using creative practices to enhance initial teacher education is emerging. One such practice is using poetry for teaching and learning in higher education and beyond. This post-qualitative article contains a dialogic exploration of our work as three teacher educators in an Australian university. The article discusses using poetry as a resource and stimulus for enhancing preservice teachers' creative, metaphorical, and critical thinking. The article is framed around our interactions and experiences of using poetry pedagogically in teacher education classes. In the article, we present three vignettes that document episodes from our classroom practice in 2019 and 2020, and we analyse and explore our use of poetry using ideas from Bakhtin and Yoshikawa. Our writing concerns poetry as a creativity modality and literacy practice in teacher education, and we argue that poetry can have affective, social, and cognitive benefits. We offer four possibilities using poetry as a creative practice and as a pedagogical tool to promote the development of innovative and literate teachers. Highlights: Developing the creative agency of new teachers through engaging with poetry. Employing poetry writing in initial teacher education to foster literacy practices. Harnessing poetry in teacher education to promote critical and creative thinking.